The retarding effect of glacier degradation on the Earth’s rotation - Wang, Chengming; Jia, Zezhong; Wen, Hao; Jiao, Shihui; Ma, Hao; Liu, Shuling; Li, Tongjun; Shen, Ruofan; Zhang, Huanhuan; Liu, Yanyan; Wang, Yongfeng; Li, Baojun (Frontiers in Earth Science, 2024)
IntroductionThe massive loss of global glacier mass caused by climate problems has caused concern, while the Earth’s rotation as the most significant form of motion has also been subtly affected. However, the quantitative effects of massive glaciers losing mass on Earth’s rotation have not been revealed.MethodsHerein, the knowledge of moment of inertia and suitable rotational inertia models in classical mechanics is initially utilized to assess the effect of quantitative glaciers losing mass on Earth's rotation.ResultsAfter specific calculations, the putative 200 billion tons of glaciers losing mass bring on an increase of 1.4099×10-4s in Earth’s rotation time in 365 days.DiscussionThis work examines the connection between glaciers losing mass and Earth’s rotation from classical mechanics, thus providing the way for investigations of relationship between climate changes and Earth.